EULAR points to consider for the definition of clinical and imaging features suspicious for progression from psoriasis to psoriatic arthritis - Zabotti, Alen; De Marco, Gabriele; Gossec, Laure; Baraliakos, Xenofon; Aletaha, Daniel; Iagnocco, Annamaria; Gisondi, Paolo; Balint, Peter V.; Bertheussen, Heidi; Boehncke, Wolf Henning; Damjanov, Nemanja S.; De Wit, Maarten; et al. (Annals of the Rheumatic Diseases, 2023)
Background: The transition from psoriasis (PsO) to psoriatic arthritis (PsA) and the early diagnosis of PsA is of considerable scientific and clinical interest for the prevention and interception of PsA. Objective: To formulate EULAR points to consider (PtC) for the development of data-driven guidance and consensus for clinical trials and clinical practice in the field of prevention or interception of PsA and for clinical management of people with PsO at risk for PsA development. Methods: A multidisciplinary EULAR task force of 30 members from 13 European countries was established, and the EULAR standardised operating procedures for development for PtC were followed. Two systematic literature reviews were conducted to support the task force in formulating the PtC. Furthermore, the task force proposed nomenclature for the stages before PsA, through a nominal group process to be used in clinical trials. Results: Nomenclature for the stages preceding PsA onset, 5 overarching principles and 10 PtC were formulated. Nomenclature was proposed for three stages towards PsA development, namely people with PsO at higher risk of PsA, subclinical PsA and clinical PsA. The latter stage was defined as PsO and associated synovitis and it could be used as an outcome measure for clinical trials evaluating the transition from PsO to PsA. The overarching principles address the nature of PsA at its onset and underline the importance of collaboration of rheumatologists and dermatologists for strategies for prevention/interception of PsA. The 10 PtC highlight arthralgia and imaging abnormalities as key elements of subclinical PsA that can be used as potential short-term predictors of PsA development and useful items to design clinical trials for PsA interception. Traditional risk factors for PsA development (ie, PsO severity, obesity and nail involvement) may represent more long-term disease predictors and be less robust for short-term trials concerning the transition from PsO to PsA. Conclusion: These PtC are helpful to define the clinical and imaging features of people with PsO suspicious to progress to PsA. This information will be helpful for identification of those who could benefit from a therapeutic intervention to attenuate, delay or prevent PsA development.
CRIS-Team Scopus Importer:2023-07-21
Keywords: inflammation; psoriatic arthritis; synovitis